Exploring factors that influence the knowledge and awareness of breastfeeding among Saudi mothers: a qualitative study - Alabdullah, Amany Anwar Saeed; ALshamy, Nasreen Mohammed; Alzahrani, Layan Majed; Safhi, Rana Abdullah; Alrashed, Mzoun Turki; Al-Mukhtalah, Layan Munahi; Alenazi, Marwa Anwar; Alzahrani, Rana Saeed; Alshammari, Ahad Turki; Alhussain, Fayzah Hussain; Alharthi, Manal Awn; Alsaran, Fidaa Mohammed (Frontiers in Nutrition, 2025)
PurposeBreastfeeding provides short- and long-term benefits for mothers and babies. Despite these advantages, the prevalence of breastfeeding among Saudi mothers is low. We explored factors affecting the knowledge and awareness of breastfeeding among Saudi mothers in Riyadh.MethodsThis qualitative study included 17 mothers. The inclusion criteria were Saudi mothers aged 18–50 years, with at least one child, living in Riyadh. Semi-structured interviews of approximately 20–40 min were conducted online or in person between March and April 2024. Data were analyzed using the constant comparative method with NVivo 11. Ethical approval was obtained from an academic institutional review board prior to data collection.ResultsTwo key themes emerged from the data. Theme 1 concerned factors facilitating knowledge and awareness of breastfeeding; subthemes included positive experience with breastfeeding, knowledge of breastfeeding, family support, and financial considerations. Theme 2 concerned factors limiting knowledge and awareness of breastfeeding; subthemes included negative experiences of breastfeeding, work situations, misconceptions, and mental health issues.ConclusionDespite the low prevalence of breastfeeding in Saudi Arabia, mothers were aware of its benefits. Physicians and midwives should provide ongoing education and support for mothers during ante- and post-natal periods to minimize misconceptions regarding breastfeeding and promote its use.